DAMPAK IMPLEMENTASI SISTEM PELAKSANA TUGAS (PLT) TERHADAP KINERJA KEPALA SEKOLAH DALAM MONITORING DAN EVALUASI DI SDN 4 SESETAN. - Ida Bagus Gede Surya Abadi; Chindytia Chindytia; Ni Luh Putu Girad Giriastana; Ni Putu Riska Warsitha Putri; Anak Agung Ratih Prabaswari (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the impact of implementing the Acting Principal (Plt) system on the performance of school principals in conducting monitoring and evaluation at SDN 4 Sesetan. This research is motivated by the importance of leadership stability in schools to support the effectiveness of school-based management (SBM), particularly in the function of monitoring and evaluating school programs. The research method used is a qualitative approach with a descriptive research type. Data were collected through semi-structured interviews, observations, and documentation techniques with the research subjects being the acting principal (Plt) and teachers at SDN 4 Sesetan. The data were analyzed through stages of data reduction, data presentation, and drawing conclusions descriptively. The results of the study indicate that the implementation of the Plt system affects the execution of monitoring and evaluation at the school. The replacement of the school principal four times within a year has caused the implementation of monitoring to lack a structured schedule, program evaluation not to be conducted routinely, and the documentation of evaluation results to remain limited. In addition, the leadership changes that occur in a short period affect coordination among school members and the continuity of school programs.